PLASMATIC IONOGRAM PROFILE OF OULED DJELLAL EWES ACCORDING TO WATER AND STRAW SALINITY AT SETIF HIGHLANDS, ALGERIA - Titaouine Mohammed; Gherissi Djalel Eddine; Mammeri Adel; Meziane Badis; Chergui Moussa; Mohamdi Hanane; Meziane Toufik (Journal of Animal and Plant Sciences, 2023)
Salty Chotts are very common in the South Highlands of Setif Governorate (northeast of Algeria). In fact, a large part of the sheep population is eventually driven to graze in these areas. However, there is no data on the mineral status of these sheep or on the mineral content of the water and fodder they consume. The present study aims to compare the plasmatic ionogram profiles of Ouled Djellal ewes reared in the Setif Highlands. For this purpose, twenty healthy ewes, aged 2 to 3 years, were selected randomly from two semi-extensive flocks, reared in two distant regions, where they are fed exclusively with locally produced straw, and watered using water with different saltiness levels: sulfated water (S) and soft water (T). Plasmatic concentrations of macroelements (Calcium "Ca", Phosphorus " P", Magnesium "Mg", Sodium "Na", Potassium "K") and trace elements (Iron "Fe", Copper "Cu", Zinc "Zn", and Manganese "Mn") were monitored monthly for one year. Ca, P, Mg, and Fe plasmatic levels were measured using a spectrophotometer, while Na and K levels were measured using flame spectrometry. The plasmatic Cu, Zn and Mn levels were measured using Graphite furnace atomic absorption spectroscopy. Results showed that plasmatic values of mineral macro elements change within standard normal ranges, with values slightly higher in Oum Ladjoul region, where the water is sulfated. Regarding the trace elements, sheep of Oum Ladjoul region were not deficient in Cu and Fe, compared to sheep of the witness region (Smara, El-Eulma). The plasmatic Zn levels were low in both regions with regard to the species norms. The absorption of sulfated water (S) seems to have a positive effect on the plasmatic level of the studied minerals. Overall, the consumed water in the study region does not seem to have an undesirable influence on the mineral metabolism. The effect of drinking water at different physiological stages and over long-term watering need to be investigated in the study region.
Keywords: Water salinity; Ouled Djellal ewes; Malnutrition; Minerals; Straw quality